Guyana In-service Distance Education (1999): A Baseline Study - The GUIDE Project and the Department for International Development (DFID) (My University, 1999)
This study is divided into four parts: Part A gives an overview of the GUIDE project, Part B presents the methodology, Part C presents the baseline data, and Part D gives the instruments recommended for use in monitoring and evaluating GUIDE or any other distance education programme for training teachers.
Keywords: Guyana in-service distance education project